Relationship between seismic and gravity anomalies at Krafla volcano, North Iceland - Le Mével, Hélène (2009)
Iceland is an emerged part of a divergent plate boundary, the mid-Atlantic ridge and situated on a hotspot, region of unusually intense and persistent volcanism (Bransdόttir et al., 2008). This location makes it a unique place to observe mechanisms resulting both from hot spot magmatism and rifting and study the oceanic crust, thanks to refraction crustal studies. In Iceland the plate boundary is expressed through different spreading segments or volcanic systems. A volcanic system is composed of a central volcano and a fissure swarm, usually between 10 km and 100 km long and up to 20 km wide (Arnott and Foulger, 1994). Krafla volcanic system is one of the five NNE-SSW elongated volcanic systems of the Northern Volcanic Zone, north of the Vatnajökull ice cap (Zeeuw-van Dalfsen et al., 2006). Magma chambers generate gravity and seismic anomalies due to the contrast of density resulting from more or less melted rocks. This report is the result of a research project, completed during the second semester of my Bachelor degree of Earth Sciences at the University of Iceland. The aim was to study the relation between the seismic anomalies and the gravity anomalies arising from the Krafla volcano. The different velocity-density systematics permit to create a density model from the seismic model using the Gravmag software. The existing literature on the crustal structure of Iceland and particularly under the Krafla central volcano gives useful constraints for the model. Different models of the crust beneath Krafla volcano are constructed, gravity anomalies generated, and the results interpreted.